Low-Cost Dielectric Substrate for Designing Low Profile Multiband Monopole Microstrip Antenna - M. R. Ahsan; M. T. Islam; M. Habib Ullah; H. Arshad; M. F. Mansor (The Scientific World Journal)
This paper proposes a small sized, low-cost multiband monopole antenna which can cover the WiMAX bands and C-band. The proposed antenna of 20 × 20 mm2 radiating patch is printed on cost effective 1.6 mm thick fiberglass polymer resin dielectric material substrate and fed by 4 mm long microstrip line. The finite element method based, full wave electromagnetic simulator HFSS is efficiently utilized for designing and analyzing the proposed antenna and the antenna parameters are measured in a standard far-field anechoic chamber. The experimental results show that the prototype of the antenna has achieved operating bandwidths (voltage stand wave ratio (VSWR) less than 2) 360 MHz (2.53–2.89 GHz) and 440 MHz (3.47–3.91 GHz) for WiMAX and 1550 MHz (6.28–7.83 GHz) for C-band. The simulated and measured results for VSWR, radiation patterns, and gain are well matched. Nearly omnidirectional radiation patterns are achieved and the peak gains are of 3.62 dBi, 3.67 dBi, and 5.7 dBi at 2.66 GHz, 3.65 GHz, and 6.58 GHz, respectively.